Body composition analysis in adolescent male athletes: Skinfold versus ultrasound - Liccardo, A.; Tafuri, D.; Corvino, A. (Journal of Human Sport & Exercise, 2021)
Introduction: Aim of this study was to compare the repeatability of the evaluation of body composition with the skinfold measuring technique and the portable ultrasound measuring technique BodyMetrix TM BX2000, in order to estimate body fat percentage in adolescents athletes. Materials e Methods: Twenty adolescent male athletes have been recruited in a basketball centre. Skinfold and ultrasound measurements were detected on the right side of the body in 2 anatomical points: triceps and subscapular. Results: The results obtained by both techniques showed a high correlation with final body fat mass (%), although differences have been observed with both methods in each anatomical site. Conclusions: The assessment of body composition is an important parameter that allows us to have an estimate of the percentage of body fat. Therefore, it is a fundamental criterion for both the professionals of wellness and the athlete, since allows to verify the results produced by dietary plans and training.